CD13 as target for tissue factor induced tumor vascular infarction in small cell lung cancer - Schmidt, Lars Henning; Muley, Thomas; Herpel, Esther; Kreuter, Michael; Thomas, Michael (Lung cancer, 2017)
Objectives: Zinc-binding protease aminopeptidase N (CD13) is expressed on tumor vascular cells and tumor cells. It represents a potential candidate for molecular targeted therapy, e.g. employing truncated tissue factor (tTF)-NGR, which can bind CD13 and thereby induce tumor vascular infarction. We performed a comprehensive analysis of CD13 expression in a clinically well characterized cohort of patients with small cell lung cancer (SCLC) to evaluate its potential use for targeted therapies in this disease. Material and methods: CD13 expression was analyzed immunohistochemically in 27 SCLC patients and correlated with clinical course and outcome. In CD-1 nude mice bearing human HTB119 SCLC xenotransplants, the systemic effects of the CD13-targeting fusion protein tTF-NGR on tumor growth were tested. Results and conclusion: In 52% of the investigated SCLC tissue samples, CD13 was expressed in tumor stroma cells, while the tumor cells were negative for CD13. No prognostic effect was found in the investigated SCLC study collective with regard to overall survival (p>0.05). In CD-1 nude mice, xenografts of CD13 negative HTB119 SCLC cells showed CD13 expression in the intratumoral vascular and perivascular cells, and the systemic application of CD13-targeted tissue factor tTF-NGR led to a significant reduction of tumor growth. We here present first data on the expression of CD13 in SCLC tumor samples. Our results strongly recommend the further investigation of tTF-NGR and other molecules targeted by NGR-peptides in SCLC patients. Considering the differential expression of CD13 in SCLC samples pre-therapeutic CD13 analysis is proposed for testing as investigational predictive biomarker for patient selection.